Dysexecutive Questionnaire (DEX): Unrestricted structural analysis in large clinical and non-clinical samples - Pedrero-Pérez, Eduardo J.; Ruiz-Sánchez-de-León, José M.; Winpenny-Tejedor, Carmen (Neuropsychological rehabilitation, 2015)
The factorial structure of the Dysexecutive Questionnaire (DEX) is an unresolved issue in scientific literature. One-to-five-factor solutions have been found in several studies by applying different research methods. Only a few of these studies used appropriate analysis procedures to suit a Likert scale-type of answer or investigated large enough samples to ensure the stability of factorial solutions. The present study examines a sample of 2151 subjects, 1482 from the general population and 669 from a clinical population. An unrestricted factorial analysis was carried out on both samples. The results unequivocally point to a single-factor solution in both samples. This means that only one latent variable is displayed in the DEX, which accounts for symptoms of oversight malfunction in activities of daily living. It is concluded that the diversity of results previously obtained in other studies may be due to using research methods that depict Likert-type scales on a continuum when they are actually ordinal categorical measures. In conclusion, the DEX should be considered a screening test that reports symptoms of prefrontal malfunction, although it is unable to specify what areas or functions have been affected, as previous studies have claimed.